1993
DOI: 10.3109/08037059309077555
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Endothelin-1 and Noradrenaline Stimulated Inositol Phosphate Formation in Cultured Aortic Smooth Muscle Cells from Spontaneously Hypertensive and Wistar Kyoto Rats

Abstract: Total [3H]-inositol phosphate formation was measured in cultured aortic smooth muscle cells from 6 and 14 week spontaneously hypertensive rats (SHR) and Wistar Kyoto (WKY) normotensive rats. Basal inositol phosphate formation was significantly increased in cells cultured from SHR compared to WKY at both 6 and 14 weeks as was basal phosphatidylinositol formation. This difference in basal values was apparent after 9 h or more incubation with [3H]-myoinositol. Both endothelin-1 and noradrenaline stimulated inosit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…Several studies in the literature have shown decreased ET-1-induced IP formation in blood vessels, including aorta, of DOCA salt-hypertensive rats or SHR Nguyen et al 1992Nguyen et al , 1993Nixon et al 1993Nixon et al , 1995Pasanisi et al 1994) which is in agreement with the present data. Moreover, ET-1 binding sites and contractile responses to ET-1 were found to be decreased in aorta of DOCA salt-hypertensive rats ) and of SHR (Clozel 1989;Dohi and Lüscher 1991).…”
Section: Discussionsupporting
confidence: 95%
“…Several studies in the literature have shown decreased ET-1-induced IP formation in blood vessels, including aorta, of DOCA salt-hypertensive rats or SHR Nguyen et al 1992Nguyen et al , 1993Nixon et al 1993Nixon et al , 1995Pasanisi et al 1994) which is in agreement with the present data. Moreover, ET-1 binding sites and contractile responses to ET-1 were found to be decreased in aorta of DOCA salt-hypertensive rats ) and of SHR (Clozel 1989;Dohi and Lüscher 1991).…”
Section: Discussionsupporting
confidence: 95%
“…Rat primary VSMCs were prepared as described previously (24), using aorta from ZA adult male Rowett Hooded‐Lister rats as the cell source. Cell purity was positively verified by Western blot analysis for α‐actin, and the absence of endothelial cell contamination was verified by Western blot analysis for von Willebrand factor (data not shown).…”
Section: Methodsmentioning
confidence: 99%